2021
DOI: 10.1123/ssj.2020-0114
|View full text |Cite
|
Sign up to set email alerts
|

Athletes as “Sites of Normative Intersectionality”: Critically Exploring the Ontology of Influence in Sport Coaching

Abstract: Social structure remains an equivocal term in (sport) sociology. Our understandings of its constitution and role in causally influencing behavior are arguably underdeveloped. Using a critical realist approach, this paper examined how structural entities and reflexive agency combined to influence behavior in an elite youth cricket context (e.g., athletes, coaches). A methodological bricolage was used to generate data and Elder-Vass’s theorizing provided the principal heuristic device. The analysis illustrated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…21 Additionally, future work may wish to focus on critical coaching (inter)actions in depth by exploring the intended influences of player-coaches’ practice as well as athletes’ perceptions of this practice using stimulated recall interviews. 28 Here, we feel that the respective theorising of Goffman 49,50 and Hochschild 51,52 could be used to understand more about the what, how, and why of player-coach behaviour. More critical understanding of the player-coach role would help to develop, support and enrich bespoke coach education opportunities that equip practitioners for the demands of their highly specific roles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Additionally, future work may wish to focus on critical coaching (inter)actions in depth by exploring the intended influences of player-coaches’ practice as well as athletes’ perceptions of this practice using stimulated recall interviews. 28 Here, we feel that the respective theorising of Goffman 49,50 and Hochschild 51,52 could be used to understand more about the what, how, and why of player-coach behaviour. More critical understanding of the player-coach role would help to develop, support and enrich bespoke coach education opportunities that equip practitioners for the demands of their highly specific roles.…”
Section: Discussionmentioning
confidence: 99%
“…26 Indeed, there is a distinct need to pay greater attention to 'athlete leadership' and the ways through which athletes make use of their own agency, within structural limits, to follow, revise, or ignore attempts by the coach to influence behaviour, action or performance. 27,28 Instead, it is claimed research largely remains leader-centric, often romanticising the role of the leader and overstating the potential power of behaviours, values, and practices as transformational or revolutionary. 29 Interpretive and critical approaches have challenged this position and have started to examine a) the social meaning of leadership, b) associated patterns of power and domination, and c) connections between broader institutional/societal conditions and leadership.…”
Section: The Role Of the Player-coach And Contemporary Critical Persp...mentioning
confidence: 99%
“…Alongside participant observations, field notes were taken by the lead researcher to record observations. As will be introduced in greater detail later in this methodology section, the Critical Incident Technique drove field notes to mark and record events which were of significance to coaches, athletes and to the researcher (Bott and Tourish 2016;Nichol et al 2021). Specifically, notes recorded what was observed in the context, from whose perspective, what was said, how coaches and athletes acted, and how others also behaved, among other things (Schensul and LeCompte 2013).…”
Section: Methodological Bricolagementioning
confidence: 99%
“…Social structure and agency are indispensable to any understanding of influence (Elder-Vass 2010). Despite this, ontological understandings of which entities at a level of social structure are responsible for influencing our behaviour and how social structure is related to agency are underdeveloped (Elder-Vass 2010; Nichol et al 2021). For instance, some have suggested that social structure equates with the term society but are then vague about defining society itself (e.g.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation